Health-related quality of life in surgical children and adolescents with congenital heart disease compared with their age-matched healthy sibling: a cross-sectional study from a lower middle-income country, Pakistan. Issue 5 (16th May 2019) - Ladak, Laila Akbar; Hasan, Babar S; Gullick, Janice; Awais, Khadija; Abdullah, Ahmed; Gallagher, Robyn
Abstract : Objective: Inconsistencies have been reported in health-related quality of life (HRQOL) in postoperative congenital heart disease (CHD). Despite the need for lifelong care due for residual symptoms, only a few studies have explored cardiac-related HRQOL but none in lower middle-income countries (LMIC). This study therefore addresses the gap by exploring HRQOL and its associated predictors in postoperative CHD in Pakistan. Outcome measures: General and cardiac-related HRQOL, associated predictors. Methods: This cross-sectional study recruited patients with CHD and age-matched healthy siblings as controls (n=129 each) at a single centre in Pakistan. Patients and their siblings completed HQROL surveys (PedsQL 4.0 Generic Core, PedsQL Cognitive Functioning). Patients only completed PedsQL 3.0 Cardiac module. Generalised linear models identified predictors. Results: The sample mean age was 8.84±3.87 years and 70% were below the poverty line for an LMIC. The majority (68%) had their first surgery after 1 year of age and were interviewed at a mean 4.08±1.91 years postoperatively. Patients with CHD had lower HRQOL in all domains compared with their age-matched siblings, with the biggest differences for total HRQOL (effect size, d=−1.35). Patients with complex CHD had lower HRQOL compared with simple to moderate CHDs in cardiac-related HRQOL. The lowest scores were for treatment problems (effect size, d=−0.91). HRQOL was worse for patients who were on cardiac medications, had complex CHD, longer cardiopulmonary bypass time, re-operations and were female. Conclusions: HRQOL issues persist in postoperative patients with CHD in LMIC, Pakistan. Solutions are needed to address poor HRQOL and lifelong concerns of patients and their parents.